Training on Digital Marketing Strategies for Palintang Hamlet MSMEs - Oktavianti, Oktavianti; Hidayat, Vinny Stephanie; Angela, Aurora; Kristiawan, Allen; Dewi, Nunik Lestari; Monalisa, Yani (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service project aims to educate Palintang Hamlet MSMEs on digital marketing. This course focuses on basic digital marketing techniques that can enhance the business operations of MSMEs in Palintang Hamlet. Palintang Hamlet hosted this training on April 15 and 29, 2025, with 25 participants. This community service uses counselling and discussion techniques. A discussion session with the trainees followed the speaker’s presentation of digital marketing-related content. It can be said that after this training, Palintang Hamlet MSME actors are better aware of digital marketing strategies.